Relationship between preoperative patient-reported outcomes and hospital length of stay: a prospective cohort study of general surgery patients in Vancouver, Canada. Issue 1 (January 2019) - Sutherland, Jason; Liu, Guiping; Crump, Trafford; Bair, Matthew; Karimuddin, Ahmer
Objectives: As an aging population drives more demand for elective inpatient surgery, one approach to reducing length of stay is enhanced evaluation of patients' preoperative health status. The objective of this research was to determine whether patient-reported outcome measures collected preoperatively can identify patients at risk for longer lengths of stay. Methods: This study was based on a prospectively recruited cohort of patients who were scheduled for elective inpatient general surgery in Vancouver, Canada. All participants completed a number of patient-reported outcome measures preoperatively, including the EQ-5D for general health status, the Patient Health Questionnaire (PHQ-9) for depression, and the pain intensity (P), interference with enjoyment of life (E), and interference with general activity (G), known as the PEG, for pain. Patient-reported outcome data were linked to hospital discharge summaries. Multivariate regression was performed to estimate risk of longer lengths of stay, adjusting for patient and clinical characteristics. The primary outcome was length of stay and its associated cost. Data collection took place between October 2012 and November 2016. Results: Participation among the population of 2307 eligible patients was 50.5%, providing 1165 participants. Preoperative patient-reported outcomes were not concordant with hospital reported diagnoses of depression or pain. Patients' preoperative depression and pain scores were independently positively associated with longer length of stay after adjusting for patient-level characteristics. Patients whose PHQ-9 score was 10, representing clinically significant depression, were estimated to have a 1.53 day longer hospitalization, which was associated with an estimated incremental hospital cost of 1667. Conclusions: Preoperative self-reported assessment of depression and pain can assist with identifying patients at higher risk of longer lengths of stay. Patient's self-reported preoperative measures of depression and pain should be incorporated into patient pathways. They provide opportunities for improving management of general surgery patients and possibly play a role in aligning hospital funding with patients' needs.